TiO2 / Ni3ZnC0.7 composite material as well as preparation method and application thereof

By uniformly dispersing the TiO2/Ni3ZnC0.7 composite material in MgH2 to form a multi-component catalyst, the problems of high hydrogen release temperature and slow kinetic properties of MgH2 hydrogen storage material are solved, efficient hydrogen absorption and discharge reaction is achieved, and the preparation process is simplified and the cost is reduced.

CN119524892AInactive Publication Date: 2025-02-28YANTAI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411644492.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

MgH2, as a hydrogen storage material, has the problem of high hydrogen release temperature and slow kinetic properties. In the prior art, the composite of TiO2 of MXene derivative sheet with non-stoichiometric carbide is less researched and the cost is higher.

Method used

The TiO2/Ni3ZnC0.7 composite material was prepared by metal gel sol and calcining method. By uniformly dispersing the composite material in MgH2, a multi-component catalyst was formed to accelerate the hydrogen absorption and discharge reaction, and the uniform dispersion of the catalyst was promoted through the presence of TiO2 sheets and carbon materials.

Benefits of technology

During the hydrogen absorption and release cycle, MgH2 and Ni3ZnC0.7 react in situ to form a multi-component catalyst, which significantly accelerates the hydrogen absorption and release reaction. The preparation process of TiO2/Ni3ZnC0.7 composite material is simple and has a low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524892A_ABST
    Figure CN119524892A_ABST
Patent Text Reader

Abstract

The invention discloses a TiO2 / Ni3ZnC0.7 composite material and a preparation method and application thereof, the TiO2 / Ni3ZnC0.7 composite material is of an independent two-dimensional lamellar structure, small particles and nanotube structures are uniformly distributed on the surface of the TiO2 / Ni3ZnC0.7 composite material, the small particles are Ni3ZnC0.7, and nanotubes have bamboo-like structures; the TiO2 / Ni3ZnC0.7 composite material with the Ni3ZnC0.7 loaded on the surface of the MXene-derived TiO2 nanosheet is obtained through a metal gel sol method and a calcination method. The method has the characteristic of simple preparation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogen storage catalyst materials, and in particular to a TiO2 / Ni3ZnC 0.7 Composite material, preparation method and application thereof. Background Art

[0002] As energy crisis and environmental pollution become increasingly serious, the development of new and efficient energy sources has become particularly important. Magnesium-based hydrogen storage alloys have attracted widespread attention due to their high hydrogen storage capacity and low cost. MgH2, as one of the most widely studied hydrogen storage materials, has attracted widespread attention due to its high theoretical hydrogen storage capacity (7.6 wt% H2) and low cost, but it has the problems of high hydrogen desorption temperature and slow kinetic properties.

[0003] In the past few years, alloying, nano-sizing, and catalyst addition have been widely used to improve the hydrogen storage performance of MgH2. Among the many methods, adding catalysts has the advantages of low cost and significant effect. Among transition metal, transition metal oxide, transition metal carbide, and transition metal sulfide catalysts, transition metal carbide catalysts have relatively greater advantages.

[0004] Studies have shown that non-stoichiometric carbides have greater advantages as catalysts than stoichiometric carbides. At the same time, among transition metal carbides, MXene-type catalysts are an effective way to enhance the hydrogen storage performance of magnesium hydride. However, there are few studies on loading non-stoichiometric carbides onto MXene-derivative lamellar TiO2 as catalysts.

[0005] In a currently reported method for preparing a Ti3C2 MXene composite hydrogen storage material (CN201811244627.6), a MXene-type catalyst is used to enhance the hydrogen storage performance of magnesium hydride, but it does not exist in the MXene derivative layer TiO2 MXene (which has a completely different physical phase) and is composited with a non-stoichiometric carbide and has a high cost. Summary of the invention

[0006] In order to overcome the above technical problems, the object of the present invention is to provide a TiO2 / Ni3ZnC 0.7 A composite material and a preparation method and application thereof. The material and the preparation method have the characteristics of simple preparation process.

[0007] The technical solution adopted by the present invention is: A TiO2 / Ni3ZnC 0.7 The composite material is a single two-dimensional layer structure with small particles and nanotube structures evenly distributed on the surface. The small particles are Ni3ZnC 0.7 , the nanotubes have a bamboo-like structure; It is easy to disperse evenly when added to MgH2; these structures make the composite material have good stability during the hydrogen absorption and desorption cycle. 0.7 In-situ reaction generates multi-component catalysts, such as Mg2Ni / Mg2NiH4, which acts as a "hydrogen pump" to accelerate the absorption and desorption of hydrogen, and the presence of TiO2 sheets and carbon materials can promote the uniform dispersion of the catalyst and prevent the agglomeration of MgH2. At the same time, a small amount of Mg-Ti-O composite oxide generated can change the Mg-H bond energy and charge distribution. The catalyst has a simple morphology and has a relatively excellent catalytic effect.

[0008] Ni3ZnC was obtained by metal gel sol and calcination method 0.7 TiO2 / Ni3ZnC loaded on the surface of MXene-derived TiO2 nanosheets 0.7 Composite materials.

[0009] A TiO2 / Ni3ZnC 0.7 A method for preparing a composite material comprises the following steps: (1) Mix hydrochloric acid and deionized water evenly, add LiF, and then add Ti3AlC2 after magnetic stirring to obtain a mixed solution; (2) taking the mixed solution obtained in step (1), stirring in a water bath, centrifuging and adjusting the pH value to obtain a precipitate which is placed in a beaker; (3) adding deionized water to the precipitate obtained in step (2) and subjecting it to ultrasonic treatment, and centrifuging the solution after ultrasonic treatment to obtain an upper suspension; (4) The upper suspension obtained in step (3) is freeze-dried to obtain Ti3C2T x ; (5) Dissolve nickel acetate tetrahydrate and zinc acetate dihydrate, terephthalic acid and triethylamine in DMF respectively, stir them evenly with a magnetic stirrer to obtain liquid A and liquid B, mix the two solutions and stir to obtain liquid C; (6) Add Ti3C2T to the liquid C obtained in step (5) x And continue to stir magnetically to obtain a gel solution; (7) The gel solution obtained in step (6) is filtered, and after the filtration is completed, it is calcined, and the calcined product is naturally cooled to obtain Ni3ZnC 0.7 TiO2 / Ni3ZnC loaded on the surface of MXene-derived TiO2 nanosheets 0.7 Composite materials.

[0010] In the step (1), the mass ratio of hydrochloric acid to deionized water is 1:3, the mass ratio of LiF to Ti3AlC2 is 1:(0.5-1.0), and the ratio of hydrochloric acid to LiF is (6-7):1. By controlling the ratio of LiF to hydrochloric acid, the amount of HF generated can be effectively controlled, thereby controlling the etching process to form an accordion morphology of a layer combination.

[0011] In the step (2), the water bath stirring temperature is 40-60°C, the stirring time is 24-48 h, the centrifugation is performed at a speed of 5000-6500 rpm, the centrifugation time is 3-10 min, and the pH value is adjusted to 6-7.

[0012] In the step (3), the ultrasonic time is 1-3 h, the centrifugation speed is 3000-4500 rpm, and the centrifugation time is 1-2 h. Setting this centrifugation parameter can achieve the Ti3C2T x Efficient collection of MXene in solution.

[0013] In step (4), the freeze drying time of the upper suspension is 20 to 36 h, and the freeze drying temperature is -40 to -50 °C. Setting this freeze drying parameter is beneficial to maintaining the Ti3C2T x The structure, properties and purity of MXene.

[0014] In the step (5), the molar ratio of nickel acetate tetrahydrate to zinc acetate dihydrate is about 1:3, the total amount is 14-15 mmol, which is dissolved in 125 mL DMF, and the magnetic stirring time is 0.3-1 h; the molar ratio of terephthalic acid to triethylamine is 1:(4.2-4.3), the total amount is 11-12 mmol, which is dissolved in 100 ml DMF (the volume ratio with the above solution is 1.25:1), and the magnetic stirring time is 0.5 h; after mixing, the C solution is magnetically stirred for 1 h.

[0015] In step (6), Ti3C2T x The mass is 0.5~1.5g, the magnetic stirring time is 1 h, and the Ti3C2T x As a key precursor material in the experiment, Ti3C2T x The molar ratio of the metal salt in liquid C is 1:(6~7).

[0016] In the step (7), the calcination temperature is 700-800° C., the holding time is 8-10 h, and the calcination atmosphere is argon.

[0017] The TiO2 / Ni3ZnC 0.7 The composite material is used as a catalyst and is mixed with magnesium hydride powder by ball milling to form a magnesium-based hydrogen storage material; The TiO2 / Ni3ZnC 0.7 The percentage of the composite material as a catalyst in the magnesium-based hydrogen storage material is 1wt%-5wt%; During the ball milling process, the material-ball ratio was 30:1, the ball milling speed was 450 rpm, and the ball milling time was 6 h.

[0018] Beneficial effects of the present invention: The present invention adopts sol-gel and calcination method to prepare a catalyst additive TiO2 / Ni3ZnC for improving the hydrogen storage performance of magnesium hydride 0.7 , the preparation method is relatively simple.

[0019] A catalyst additive TiO2 / Ni3ZnC for improving the hydrogen storage performance of magnesium hydride prepared by the present invention 0.7 The morphology is a single two-dimensional sheet structure, with small particles and nanotube structures evenly distributed on the surface. The nanotubes are bamboo-shaped, with a simple morphology and a relatively excellent catalytic effect.

[0020] The present invention adds the catalyst into MgH2, and can make the catalyst evenly dispersed on the surface of MgH2 by ball milling to obtain better catalytic performance, and solves the problem of uneven catalyst dispersion. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The TiO2 / Ni3ZnC obtained in Example 1 0.7 Scanning electron microscopy images of the composite materials.

[0022] Figure 2 The TiO2 / Ni3ZnC obtained in Example 1 0.7 Composite material and Ti3C2T after etching x X-ray diffraction spectrum of .

[0023] Figure 3 MgH2-2.5 wt% TiO2 / Ni3ZnC obtained in Example 4 0.7 Graph showing the hydrogen absorption kinetics of the material at different temperatures.

[0024] Figure 4 MgH2-2.5 wt% TiO2 / Ni3ZnC obtained in Example 4 0.7 Hydrogen desorption kinetics of the material at different temperatures. DETAILED DESCRIPTION

[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] In the following examples, the instruments and equipment used and their uses are as follows: Vacuum filtration equipment: SHB-IIIS, sample separation; Vacuum freeze dryer: FD-1200, sample freeze drying; Ultrasonic cleaner: KQ-50E-2L, sample dispersion; Centrifuge: TG18G, sample separation; Tube furnace: OTF-1200X, sample calcination; X-ray diffractometer: Shimadzu XRD-7000, sample phase analysis; Scanning electron microscope: JEOL JSM-7610F, sample morphology analysis; Transmission electron microscope: FEI-TALOS-F200X, sample morphology analysis; Test equipment: Sieverts-type, hydrogen storage performance test. Example

[0027] (1) Mix 15 mL of hydrochloric acid and 5 mL of deionized water, add 1.6 g of LiF, stir magnetically for 10 minutes, then add 1 g of Ti3AlC2 to obtain a mixed solution; (2) taking the mixed solution obtained in step (1), stirring in a water bath at 40° C. for 24 h, and then centrifuging at 6000 rpm for 5 min, and adjusting the pH value to 6-7 to obtain a precipitate; (3) Take the precipitate obtained in step (2), add 50 mL of deionized water, perform ultrasonic treatment for 2 h, and then centrifuge at 4000 rpm for 1 h to obtain an upper suspension; (4) The upper suspension obtained in step (3) was freeze-dried for 24 h at a freeze-drying temperature of -43 °C to obtain Ti3C2T x ; (5) Dissolve 10-12 mmol nickel acetate tetrahydrate and 2-4 mmol zinc acetate dihydrate in 125 mL DMF, respectively, and stir magnetically for 0.5 h to obtain solution A. Dissolve 7-10 mmol terephthalic acid and 1-3 mL triethylamine in 100 mL DMF, and stir magnetically for 0.5 h to obtain solution B. Mix solution A and solution B, and stir magnetically for 1 h to obtain solution C. (6) Add 0.6 g Ti3C2T to the solution C obtained in step (5). x , and continue magnetic stirring for 1 hour to obtain a gel solution; (7) The gel solution obtained in step (6) was filtered and calcined at 700°C for 10 h, and then naturally cooled to obtain TiO2 / Ni3ZnC 0.7 Composite materials.

[0028] The obtained Ti3C2T x and TiO2 / Ni3ZnC 0.7 Composite materials were characterized by X-ray diffraction, such as Figure 1 As shown. By Ni3ZnC 0.7 By comparing with the standard PDF card, it can be determined that the three obvious diffraction peaks at 42.7°, 49.8° and 73.1° belong to Ni3ZnC 0.7 ,like Figure 1 (a) shown. Figure 1 (b) shows Ti3C2T x The XRD spectrum shows that the broad diffraction peaks at 6° and 61° belong to Ti3C2T x The multiple diffraction peaks detected at 27.4°, 36.1°, 39.2°, 41.2°, 44.0°, 54.3°, 56.6° and 69.0° belong to TiO2. The above results prove that this method successfully synthesized TiO2 / Ni3ZnC 0.7 , and Ti3C2T x TiO2 was generated in situ by oxidation during the calcination process. 0.7 The morphology of the composites was characterized, such as Figure 2 As shown, it can be seen that some small particles and nanotube structures are evenly distributed on the surface of the lamellar structure. The particle size is approximately concentrated in the range of 70~100nm, the nanotube diameter is about 10nm, and the length varies from 100-500nm. Example

[0029] (1) Mix 15 mL of hydrochloric acid and 5 mL of deionized water, add 1.6 g of LiF, stir magnetically for 10 minutes, then add 1.2 g of Ti3AlC2 to obtain a mixed solution; (2) taking the mixed solution obtained in step (1), stirring in a water bath at 40° C. for 24 h, and then centrifuging at 6000 rpm for 5 min, and adjusting the pH value to 6-7 to obtain a precipitate; (3) Take the precipitate obtained in step (2), add 50 mL of deionized water, perform ultrasonic treatment for 2 h, and then centrifuge at 4000 rpm for 1 h to obtain an upper suspension; (4) The upper suspension obtained in step (3) was freeze-dried for 24 h at a freeze-drying temperature of -43 °C to obtain Ti3C2T x ; (5) Dissolve 10-12 mmol nickel acetate tetrahydrate and 2-4 mmol zinc acetate dihydrate in 125 mL DMF, respectively, and stir magnetically for 0.5 h to obtain solution A. Dissolve 7-10 mmol terephthalic acid and 1-3 mL triethylamine in 100 mL DMF, and stir magnetically for 0.5 h to obtain solution B. Mix solution A and solution B, and stir magnetically for 1 h to obtain solution C. (6) Add 1g Ti3C2T to the solution C obtained in step (5). x , and continue magnetic stirring for 1 hour to obtain a gel solution; (7) The gel solution obtained in step (6) was filtered and calcined at 700°C for 10 h, and then naturally cooled to obtain TiO2 / Ni3ZnC 0.7 Composite materials. Example

[0030] (1) Mix 15 mL of hydrochloric acid and 5 mL of deionized water, add 1.6 g of LiF, stir magnetically for 10 minutes, then add 1.5 g of Ti3AlC2 to obtain a mixed solution; (2) taking the mixed solution obtained in step (1), stirring in a water bath at 40° C. for 24 h, and then centrifuging at 6000 rpm for 5 min, and adjusting the pH value to 6-7 to obtain a precipitate; (3) Take the precipitate obtained in step (2), add 50 mL of deionized water, perform ultrasonic treatment for 2 h, and then centrifuge at 4000 rpm for 1 h to obtain an upper suspension; (4) The upper suspension obtained in step (3) was freeze-dried for 24 h at a freeze-drying temperature of -43 °C to obtain Ti3C2T x ; (5) Dissolve 10-12 mmol nickel acetate tetrahydrate and 2-4 mmol zinc acetate dihydrate in 125 mL DMF, respectively, and stir magnetically for 0.5 h to obtain solution A. Dissolve 7-10 mmol terephthalic acid and 1-3 mL triethylamine in 100 mL DMF, and stir magnetically for 0.5 h to obtain solution B. Mix solution A and solution B, and stir magnetically for 1 h to obtain solution C. (6) Add 1.5 g Ti3C2T x , and continue magnetic stirring for 1 hour to obtain a gel solution; (7) The gel solution obtained in step (6) was filtered and calcined at 700°C for 10 h, and then naturally cooled to obtain TiO2 / Ni3ZnC 0.7 Composite materials. Example

[0031] Contains 2.5 wt% TiO2 / Ni3ZnC 0.7 Preparation of Mg-based hydrogen storage materials with composite catalysts: Take 0.1g of TiO2 / Ni3ZnC obtained in Example 1 0.7 The composite material and 3.9g MgH2 powder were put into a ball mill with a ball-to-material ratio of 30:1 and ball milled at 450rpm for 6h to finally obtain a 2.5% TiO2 / Ni3ZnC 0.7 Mg-based hydrogen storage material of composite catalyst, denoted as MgH2-2.5 wt% TiO2 / Ni3ZnC 0.7 , and used for hydrogen absorption and desorption kinetics testing.

[0032] The obtained MgH2-2.5 wt% TiO2 / Ni3ZnC 0.7 The kinetic performance test of hydrogen absorption and desorption was carried out, and the test data were as follows Figure 3 and Figure 4 As shown, the present invention adds TiO2 / Ni3ZnC 0.7 The performance of the catalyst is greatly improved compared with pure MgH2: MgH2-2.5 wt% TiO2 / Ni3ZnC 0.7 In terms of hydrogen absorption, at 423 K, MgH2-2.5 wt% TiO2 / Ni3ZnC 0.7 The composite material can quickly absorb 3.94 wt% H2 within 200 s. In terms of hydrogen release, at 673 K, MgH2-2.5 wt% TiO2 / Ni3ZnC 0.7The amount of hydrogen released by the composite material can reach 6.11 wt% within 300 s, and when the temperature is reduced to 623 K, 5.95 wt% of H2 can be released within 1200 s. Under the same conditions, it has a significant improvement compared with pure MgH2. Example

[0033] Containing 1 wt% TiO2 / Ni3ZnC 0.7 Preparation of Mg-based hydrogen storage materials with composite catalysts: Take 0.04g of TiO2 / Ni3ZnC obtained in Example 1 0.7 The composite material and 3.96g MgH2 powder were put into a ball mill with a ball-to-material ratio of 30:1 and ball milled at 450rpm for 6h to finally obtain a TiO2 / Ni3ZnC catalyst containing 1% composite material. 0.7 Mg-based hydrogen storage material, denoted as MgH2-1 wt% TiO2 / Ni3ZnC 0.7 , and used for hydrogen absorption and desorption kinetics testing.

[0034] The test results are similar to those of Example 4. The present invention adds TiO2 / Ni3ZnC 0.7 The performance of the catalyst is greatly improved compared with pure MgH2. Example

[0035] Contains 5 wt% TiO2 / Ni3ZnC 0.7 Preparation of Mg-based hydrogen storage materials with composite catalysts: Take 0.2g of TiO2 / Ni3ZnC obtained in Example 1 0.7 The composite material and 3.8g MgH2 powder were put into a ball mill with a ball-to-material ratio of 30:1 and ball milled at 450rpm for 6h to finally obtain a TiO2 / Ni3ZnC catalyst containing 5% of the composite material. 0.7 Mg-based hydrogen storage material, denoted as MgH2-5 wt% TiO2 / Ni3ZnC 0.7 , and used for hydrogen absorption and desorption kinetics testing.

[0036] The test results are similar to those of Example 4. The present invention adds TiO2 / Ni3ZnC 0.7 The performance of the catalyst is greatly improved compared with pure MgH2.

[0037] The above are only embodiments of the present invention and are not intended to limit the protection scope of the present invention. It should be pointed out that for those skilled in the art, any modification, equivalent replacement, improvement, etc. made without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A TiO2 / Ni3ZnC 0.7 A composite material, characterized in that It presents a separate two-dimensional sheet structure, with small particles and nanotube structures evenly distributed on the surface. The small particles are Ni3ZnC 0.7 , the nanotubes have a bamboo-like structure; Ni3ZnC was obtained by metal gel sol and calcination 0.7 TiO2 / Ni3ZnC loaded on the surface of MXene-derived TiO2 nanosheets 0.7 Composite materials.

2. A TiO2 / Ni3ZnC according to claim 1 0.7 A method for preparing a composite material, characterized in that: The steps include: (1) Mix hydrochloric acid and deionized water evenly, add LiF, and then add Ti3AlC2 after magnetic stirring to obtain a mixed solution; (2) taking the mixed solution obtained in step (1), stirring in a water bath, centrifuging and adjusting the pH value to obtain a precipitate which is placed in a beaker; (3) adding deionized water to the precipitate obtained in step (2) and subjecting it to ultrasonic treatment, and centrifuging the solution after ultrasonic treatment to obtain an upper suspension; (4) The upper suspension obtained in step (3) is freeze-dried to obtain Ti3C2T x ; (5) Dissolve nickel acetate tetrahydrate and zinc acetate dihydrate, terephthalic acid and triethylamine in DMF respectively, stir them evenly with a magnetic stirrer to obtain liquid A and liquid B, mix the two solutions and stir to obtain liquid C; (6) Add Ti3C2T to the liquid C obtained in step (5) x And continue magnetic stirring to obtain a gel solution; (7) The gel solution obtained in step (6) is filtered, and after the filtration is completed, it is calcined, and the calcined product is naturally cooled to obtain Ni3ZnC 0.7 TiO2 / Ni3ZnC loaded on the surface of MXene-derived TiO2 nanosheets 0.7 Composite materials.

3. A TiO2 / Ni3ZnC according to claim 2 0.7 A method for preparing a composite material, characterized in that: In the step (1), the mass ratio of hydrochloric acid to deionized water is 1:3, the mass ratio of LiF to Ti3AlC2 is 1:(0.5-1.0), and the ratio of hydrochloric acid to LiF is (6-7):

1.

4. A TiO2 / Ni3ZnC according to claim 2 0.7 A method for preparing a composite material, characterized in that: In the step (2), the water bath stirring temperature is 40-60°C, the stirring time is 24-48 h, the centrifugation is performed at a speed of 5000-6500 rpm, the centrifugation time is 3-10 min, and the pH value is adjusted to 6-7.

5. A TiO2 / Ni3ZnC according to claim 2 0.7 A method for preparing a composite material, characterized in that: In the step (3), the ultrasonic time is 1 to 3 h, and the centrifugation speed is 3000 to 4500 rpm, and the centrifugation time is 1 to 2 h.

6. A TiO2 / Ni3ZnC according to claim 2 0.7 A method for preparing a composite material, characterized in that: In the step (4), the freeze-drying time of the upper suspension is 20 to 36 hours, and the freeze-drying temperature is -50 to -60°C.

7. A TiO2 / Ni3ZnC according to claim 2 0.7 A method for preparing a composite material, characterized in that: In the step (5), the molar ratio of nickel acetate tetrahydrate to zinc acetate dihydrate is about 1:3, the total amount is 14-15 mmol, which is dissolved in 125 mL DMF and the magnetic stirring time is 0.3-1 h; the molar ratio of terephthalic acid to triethylamine is 1:(4.2-4.3), the total amount is 11-12 mmol, which is dissolved in 100 ml DMF (the volume ratio with the above solution is 1.25:1), and the magnetic stirring time is 0.5 h; after mixing, the C solution is magnetically stirred for 1 h.

8. A TiO2 / Ni3ZnC according to claim 2 0.7 A method for preparing a composite material, characterized in that: In step (6), Ti3C2T x The mass is 0.5~1.5g, the magnetic stirring time is 1 h, and the Ti3C2T x As a key precursor material in the experiment, Ti3C2T x The molar ratio of the metal salt in liquid C is 1:(6~7).

9. A TiO2 / Ni3ZnC according to claim 2 0.7 A method for preparing a composite material, characterized in that: In the step (7), the calcination temperature is 700-800° C., the holding time is 8-10 h, and the calcination atmosphere is argon.

10. The TiO2 / Ni3ZnC according to any one of claims 1 to 9 0.7 The application of composite materials is characterized by: The TiO2 / Ni3ZnC 0.7 The composite material is used as a catalyst and is mixed with magnesium hydride powder by ball milling to form a magnesium-based hydrogen storage material; The TiO2 / Ni3ZnC 0.7 The percentage of the composite material as a catalyst in the magnesium-based hydrogen storage material is 1wt%-5wt%; During the ball milling process, the material-ball ratio was 30:1, the ball milling speed was 450 rpm, and the ball milling time was 6 h.

Citation Information

Patent Citations

  • Preparation method of Ti3C2MXene composite hydrogen storage material

    CN109467047A

  • Bimetal carbide M3ZnCx powder material as well as preparation method and application thereof

    CN114939426A